Genetic characterization of African swine fever virus in Cameroon, 2010–2018 - (:unkn) unknown (My University, 2019)
African swine fever (ASF) is a highly lethal haemorrhagic disease in domestic and wild swine that has acquired great importance in sub-Saharan Africa since 1997. ASF was first reported in Cameroon in 1982 and was detected only in Southern Cameroon (South, West, East, Northwest, Southwest, Littoral, and Centre regions) until February 2010 when suspected ASF outbreaks were reported in the North and Far North regions. We investigated those outbreaks by analysing samples that were collected from sick pigs between 2010 and 2018. We confirmed 428 positive samples by ELISA and real-time PCR and molecularly characterized 48 representative isolates. All the identified virus isolates were classified as ASFV genotype I based on the partial B646L gene (C-terminal end of VP72 gene) and the full E183L gene encoding p54 protein analysis. Furthermore, analysis of the central variable region (CVR) within the B602L gene demonstrated that there were 3 different variants of ASFV genotype I, with 19, 20, and 21 tetrameric tandem repeat sequences (TRSs), that were involved in the 2010–2018 outbreaks in Cameroon. Among them, only variant A (19 TRSs) was identical to the Cam/82 isolate found in the country during the first outbreaks in 1981–1982. This study demonstrated that the three variants of ASFV isolates involved in these outbreaks were similar to those of neighbouring countries, suggesting a movement of ASFV strains across borders. Designing common control measures in affected regions and providing a compensation programme for farmers will help reduce the incidence and spread of this disease.
Keywords: African Research